THE PROFESSIONALISM OF THE SUBDISTRICT LEADER IN THE COORDINATION OF THE SOUTHERN PART OF THE SOUTH OF THE TALAUD ISLANDS DISTRICT - NAE, VALENTIN; ROMPAS, WELSON; MAMBO, RULLY (JURNAL ADMINISTRASI PUBLIK, 2018)
Profesionalism is a reflection of the skills and expertise of the apparatus that can be effective if supported bythe suitability of the level of knowledge on the basis of educational background with the workload that becomesthe responsibility. The success of development will be seen from thr high productivity of the prosperouspopulation and evenly distributed. To bring about socio-culturan change of society, it is the duty of allgovernment apparatus and society it self to create and expand and implement the national developmentprograms thet are held. To measure professionalism, it can be used some measure professionalism, Whichincludes : Knowladge,Skill,expertise. This research uses data collection techniques that qualitative descriptiveresearch through data collection tecniques that is data reduction,Data presentation,and conclusion.Profesionalism is an attitude or circumstance in carrying out the work with the need for expertise. In this studythe professionalism of the subdistrict leader in coordinating the area of southern Essang Talaud archipelagodistcrit is seen from the indicators namely: ability,Skill,ExpertiseKeywords : Profesionalism of the subdistrict laeder